Production of Lactic Acid and Polyhydroxyalkanoates (PHA) from Restaurant Waste - Kassim, Hafizah (2001)
In this study, restaurant waste was used as a substrate for the production of lactic acid and polyhydroxyalkanoate (PHA) by Ralstonia eutropha (formerly known as Alcaligenes eutrophus). PHA production was achieved via a two-stage process; lactic acid production from restaurant waste followed by PHA production from lactic acid. In the first stage, the study was focused on optimization of culture condition for lactic acid production in batch anaerobic treatment. These treatments were carried out in a 2L stirred-tank bioreactor with lL working volume. The pH was controlled using a pH controller by adding 3M NaOH automatically. The lactic acid produced was determined by HPLC method. Optimization for best conditions of lactic acid production were done on temperature, duration at controlled pH 7, seeding with appropriate inoculum and culture under sterile and non-sterile conditions. Lactic acid was dominantly produced (70-99%) during most of the anaerobic treatments followed by acetic (1-20%), butyric (0-8%) and propionic acid (0-1%). Among the three different temperatures investigated i.e. 30°C, 37°C and 4SoC, 37°C was the best for lactic acid production (17 g/L). Studies on the effect of duration at controlled pH 7 showed that by controlling pH 7 for 12 hours, higher lactic acid was produced (40 g/L). Production of lactic acid was reduced when pH 7 was controlled for longer period due to methanogenesis. Seeding with Lactobacillus rhamnosus results in higher production of lactic acid (67 g/L). Increased concentration of lactic acid was detected under sterile condition. In this study, the maximum concentration of lactic acid produced from restaurant waste was 97.7 g/L when the temperature was controlled at 37°C, controlled pH 7 throughout the experiment and seeded with L. rhamnosus under sterile condition. The supernatant collected from the treatment of highest lactic acid production was used in the second stage for the production of polyhydroxyalkanoate. PHA was produced by Ralstonia eutropha strain ATCC 17699 in a 2L bioreactor (l L working volume) in batch culture, using lactic acid as the sole carbon source during the production phase. The bacteria was first precultivated in a nutrient-rich medium for 24 h before inoculation into the production medium i.e. treated restaurant waste containing 20-25 g/L lactic acid as the carbon source. Initial inoculum cell density was kept high at 4-5 g/L. The maximum PHA concentration obtained after 70h was about 10 g/L, corresponding to 97% (gig) of cell dry weight.